GLOBAL CONSCIOUSNESS AS A SOCIOCULTURAL PRACTICE - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the phenomenon of global consciousness and its cultural, historical and civilizational dimensions.